Elevating Arabic Vocabulary Learning: Integrating Teams Games Tournament and Show & Tell Method - Hasanah, Mamluatul; Hasibuan, Renni; Jundi, Muhammad (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
This research aims to measure the effectiveness of using TGT (Teams-Games-Tournaments) and S&T (Show and Tell) methods in improving students' mastery of Arabic vocabulary at Madrasah Tsanawiyyah Negeri (MTsN) 1 in Kota Batu, Malang, East Java. This research utilizes a quantitative methodology employing a quasi-experimental pre-test and post-test control group design. The collected data undergo analysis through descriptive statistical tests, assessments for normality using the Kolmogorov-Smirnov test, and independent sample t-test. Compared to the control group, the results show a significant improvement in Arabic vocabulary mastery among students involved in the experimental group receiving TGT and S&T treatments. These findings highlight the potential of a collaborative approach between TGT and S&T methods in creating a dynamic and engaging learning environment, enhancing students' comprehension through group interaction and competitive activities. Additionally, literature supports the effectiveness of TGT and S&T methods in improving learning outcomes and student motivation. Thus, this research makes a significant contribution to enriching understanding of the use of innovative teaching approaches in language learning contexts, as well as providing a solid foundation for more effective pedagogical approaches in the future.